Physical, mechanical and antimicrobial properties of starch films incorporated with ε-poly-l-lysine. (1st January 2015) - Zhang, Liming; Li, Ruichao; Dong, Feng; Tian, Aiying; Li, Zhengjun; Dai, Yujie
Highlights: Starch was incorporated with ε -poly-l -lysine ( ε -PL) to prepare films. Interactions between starch and ε -PL can affect the physical properties of films. Developed films exhibited strong antimicrobial activity against bacteria. Starch/ ε -PL films exhibited low antimicrobial effects against Aspergillus niger . Abstract: Starch/ ε -poly-l -lysine ( ε -PL) composite films were prepared by combining 4% (w/v) gelatinized cornstarch and varying the level of ε -PL. The physical, mechanical and antimicrobial properties of these films were investigated. Fourier-transform infrared spectra (FT-IR) showed that the carbonyl group stretching vibration band of the ε -PL molecule shifted from 1646 cm −1 to 1673 cm −1 in the composite films. Differential scanning calorimetry (DSC) results indicated that there were sharp endothermal peaks at 215–230 °C for the composite films. These results indicated that there was an intense interaction between the two components. The films incorporated with ε -PL showed a higher tensile strength (TS) and elongation-at-break ( E ) than those of the starch film alone. These composite films exhibited effective inhibition against Escherichia coli and Bacillus subtilis, films containing 2% (w/w) ε -PL effectively suppressed the growth of the tested microbes ( P  < 0.05). The starch/ ε -PL films showed a low inhibitory effect on Aspergillus niger . This antimicrobial trend of the composite films was in agreement with the results of free ε -PL.